Environmental Safety of Modern Kazakhstan: General Legal Analysis - KOSHKINBAEVA, Aliya S.; ZHUMAGULOVA, Sholpan R.; ZHANALIYEVA, Aigul Z.; BIZHANOVA, Aigul R.; KHAMZINA, Sholpan S. (Journal of Environmental Management and Tourism, 2019)
World experience shows that greening the entire socio-economic system of any state is the basis for successful solving of environmental problems and preventing environmental disasters. Environmental safety, as a component of national security, is an indispensable condition for sustainable development and is the basis for the preservation of natural systems and the maintenance of appropriate environmental quality. The Kazakhstan political and legal mechanism for ensuring environmental security against the background of multilateral and dynamically evolving international institutions has not achieved any significant efficiency yet. For many decades, Kazakhstan has developed a predominantly natural resource management system with extremely high technogenic pressure on the environment. Therefore, a fundamental improvement in the ecological situation has not occurred yet, and it is still characterized by the degradation of natural systems, which leads to a destabilization of the biosphere, a loss of its ability to maintain the quality of the environment, which is necessary for the community life. The article presents conclusions on the current list of threats to national security in the environmental field relevant for Kazakhstan. Specific offer has been made to improve the mechanisms for ensuring environmental safety, which includes: improving the efficiency of state control in the environmental protection and environmental management; optimization of licensing system of environmental management and environmental expertise; improvement of the environmental monitoring system; ecologization of legislation; systematization of legislation in the field of protection the environment; expansion of international cooperation.